Human CD4+ Memory T Cells Are Preferential Targets for Bystander Activation and Apoptosis - Sarah C. Bangs; Dilair Baban; Helen Cattan; Chris Ka-Fi Li; Andrew J. McMichael; Xiao‐Ning Xu (2009)
Abstract There is much evidence that T cells may be activated via mechanisms that act independently of direct TCR ligation. Despite this, the question of whether such forms of bystander T cell activation occur during immune responses is hotly debated. To address some outstanding questions, we set up an in vitro system within which to analyze bystander T cell activation in human T cells, in the absence of the possibility for TCR cross-reactivity. In addition, we have investigated the genetic, phenotypic, and functional characteristics of bystander-activated T cells. In this study, we show that bystander T cell activation is, indeed, observed during a specific immune response, and that it occurs preferentially among CD4+ memory T cells. Furthermore, bystander-activated T cells display a distinct gene expression profile. The mechanism for bystander T cell activation involves soluble factors, and the outcome is an elevated level of apoptosis. This may provide an explanation for the attrition of T cell memory pools of heterologous specificity during immune responses to pathogens such as viruses.